Challenges of Fetal Rights under Economic Hardship: A Qualitative Study from Iran - panjalipour, sepideh; Mosadeghrad, Ali Mohamad; Mirmolaei, Seyede Tahereh; Abbassi, Mahmoud; Shahbazi Sighaldeh , shirin (Bioethics and Health Law Journal (BHL), 2026)
While fetal rights are gaining momentum in global health, ethics and legal discourses, they are still below par in socioeconomic policy frameworks. Access to prenatal services and family decision-making in Iran faces increased challenges due to both current international economic sanctions and recently introduced pronatalist population policies that have intersected with long-standing structural economic hardships. This study investigates the challenges concerning fetal rights in the context of Iranian families' economic difficulties. The focused qualitative analysis was derived from the broader mixed-methods research titled “Policy Analysis for Developing a Charter of Fetal Rights in Iran”. Semi-structured, in-depth interviews were conducted with 25 participants (5 parents, 6 healthcare providers, 4 legal experts, 4 religious scholars and 6 policy specialists). Key informants such as legal experts, theologians and policymakers were recruited using purposive sampling to ensure diversity of professional perspectives, while snowball sampling was applied primarily for parents due to accessibility challenges. Recruitment continued until data saturation was reached. Data analysis was performed using the conventional content analysis method by Zhang and Wildemuth in eight stages, supported by the MAXQDA software (version 2020). Content analysis revealed that the central theme was “Fetal Rights in the Context of Economic Hardship”, which encompassed four interrelated subcategories: 1. Financial barriers to accessing specialized prenatal screening services under limited insurance coverage; 2. Occupational insecurity and informal employment conditions during pregnancy; 3. Anticipatory economic anxiety regarding long-term childrearing expenses under unstable economic conditions; 4. Insufficient institutional welfare mechanisms and fragmented family-based support systems. The factors of economic vulnerability were found to be one of the structural determinants affecting maternal well-being and fetal health outcomes. Economic hardship and insufficient structural support indirectly affect maternal physical and mental health, thereby constraining the realization of fetal rights. Economic safety nets should therefore be incorporated into maternal and fetal health policies, including expanded insurance coverage for prenatal diagnostic services and targeted financial and nutritional programs for economically disadvantaged pregnant women.